Effects of cyclic dislodgement on the retentive force reduction of different ot-equator caps and removal torque of the retentive components of a mini dental implant system - T. Rattanadech (2020)
© 2019, CIC Edizioni Internazionali s.r.l.. All rights reserved. Purpose. The aim of this study was to evaluate the retentive force and the removal torque of the OT-Equator® retentive components on mini dental implant under cyclic dislodgement at different angulations. Methods. Fifty models of PW Plus® mini implants and OT-Equator® attachments were divided into 2 groups based on implant angulations (Group 1 = 0°, 2 = 15°). Each group was divided into 5 subgroups based on the weight-color coded of the retentive caps (black, yellow, pink, white and violet). Cyclic dislodgement was carried out for a total of 2,880 cycles. The retentive force was recorded at 0, 360, 720, 1,440 and 2,880 cycles. After the final cycle, the removal torque was measured. The data were analysed using One-way ANOVA and t-test with the significant set at P < 0.05. Results. The increase in cyclic dislodgement significantly reduced the retentive force of OT-Equator® retentive caps at 15° compared to that at 0°, except for the black cap. The removal torque also significantly decreased after 2,880 cycle compared to the insertion. There were no significant differences in removal torque at different angulations. Conclusions. Increases in the number of dislodgement cycles and implant angulation significantly decrease the retentive force of OT-Equator®. However, the implant angulation did not have significant influence on removal torque. OT-Equator ® with increased implant angulation require regular follow-up each year and screw re-tightening should be considered.